Swinging for the fences: How Comprehensive Drug Testing, Inc. missed the ball on digital searches. - Angermeier, Vincent (Journal of Criminal Law & Criminology)
This Comment offers a critical analysis of the recent decision of the Ninth Circuit Court of Appeals in United States v. Comprehensive Drug Testing, Inc. First, the Comment discusses the facts of the case and the decisions leading up to the en banc decision. The Comment goes on to review the evolution and purposes of the plain view doctrine. The Comment then argues that the Ninth Circuit's decision in Comprehensive Drug Testing, Inc. represents an overreaction to the privacy concerns raised by the application of the plain view doctrine to digital searches. Finally, it will advocate that courts continue to apply the plain view doctrine to digital searches, subject to heightened scrutiny by judges, who should grant warrants only when it is reasonable to do so in light of the strength of the probable cause, the severity of the crime being investigated, and voluntary actions taken by the government to reduce the social cost of the privacy intrusion. Reprinted by permission of the publisher.